Low-latency and zero-copy message passing protocols for SCI-based clusters - Oliveira, Fábio A. D.; Ávila, Rafael B.; Barreto, Marcos E.; Navaux, Philippe O. A. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2001)
This paper presents the design and implementation of three message passing protocols, whose development aimed at efficiently exploiting the high-performance capabilities of the SCI interconnect. These protocols are compared to the communication mechanisms adopted by MPI implementations for SCI clusters. The performance of the proposed protocols allows us to state that they are more efficient, in terms of latency and bandwidth, than the correspondent communication strategies employed by existing MPI implementations specifically designed for SCI-connected clusters.